Repertório de saberes da profissionalidade docente : elementos para uma pedagogia ambiental - Dantas, Jonielton Oliveira (2022)
Environmental education, despite being an already consolidated conceptual field, with welldefined principles and objectives that place it in a central position in the process of change for sustainable development, has not been able to enhance the transformation it proposes concerning awareness, sensitization, and change of attitude of people in the face of socioenvironmental issues, nor to assume the vanguard of the necessary transformations in school education itself. Regarding formal education, several explanations are given for the failure of environmental education, with teacher training being pointed out as one of the most problematic points. This study defends the thesis that the effectiveness of environmental education in the context of formal education presupposes a pedagogy that provides support, a pedagogy aligned with complex thinking, which assumes the complexity of educational processes concerning the environmental dimension, a pedagogy environmental. From this perspective, this research aimed to develop guidelines for an environmental pedagogy based on the mobilization of the repertoire of knowledge of teaching professionalism through didactic-pedagogical strategies for the continuing education of teachers in environmental education. In this perspective, this research had as general objective to develop the guidelines of an environmental pedagogy from the mobilization of the repertoire of knowledge of the teaching profession through didacticpedagogical strategies of continuous formation of teachers in environmental education. To meet this proposition, a qualitative approach was chosen, anchored in assumptions and procedures related to action research through the development of a course called Training Process in Environmental Education and Teaching Professionalization as the main strategy to promote dialogue of knowledge about education and the environment between the researcher and the teachers who teach in Basic Education in public schools located in municipalities that are part of the Regional Board of Education - 02 (DRE-02) of the State Department of Education and Culture of the State of Sergipe (SEDUC/SE). The action contemplated six stages, in which data collection procedures and instruments adapted to digital tools were used, such as questionnaires (on-line form), document analysis - applied to the 'chat' messages generated in the 'online' meetings ' (Meet), in the discussion forums (Classroom), and the recordings of the videoconferences. The content produced in this process was submitted to the Content Analysis technique, to infer an interpretation of the resulted that meet the problems and objectives defined for this research. The results obtained reveal a diversity of knowledge that make up the repertoire of teaching professionalism, effectively contributing to the elaboration of theoreticalpractical guidelines for environmental pedagogy, with the potential to transfer to different geocultural contexts. Furthermore, as a product of this study an itinerary for implementing environmental pedagogy in schools is presented to support decision-making and adoption of strategies by managers and teachers.